Investigation of the Relationship Between the Coach - Athlete Relationship and Sport Confidence in Adolescent Elite Taekwondo Athletes - Ayşegül Funda ALP; Ramazan TAŞÇIOĞLU; Serdar KOCAEKŞİ; Umut SEZER (Pamukkale Spor Bilimleri Dergisi, 2021)
The purpose of this study is to investigate adolescent taekwondo athletes the relationship between coach-athlete relations and sport confidence in terms of gender. A total of 108 athletes (X̄age=14.73±1.43), 52 females (X̄age=14.98±1.42), 56 males (X̄age=14.50±1.41) participated in the study voluntarily. Data were collected with the demographic form, coach-athlete relationship questionnaire, and sport confidence inventories. Descriptive analysis, Mann-Whitney U test, and Spearman rho correlation analysis were used to analyze the data. There was no significant difference between the female and male athletes in all subscales of the coach-athlete relationship questionnaire and sport confidence inventories (p>.05). As a result of the Spearman correlation analysis, while there was a moderate positive correlation between the closeness subscale of the coach-athlete relationship questionnaire and trait sport confidence (r=.35, r2=.12, p<.05) and state sport confidence (r=.34, r2=.12, p<.05); there was no correlation between commitment and complementarity subscales and sport confidence inventories in female athletes (p>.05). In male athletes, there was no significant correlation between the subscales of the coach-athlete relationship questionnaire and the sport confidence inventories (p>.05). In conclusion, while the closeness of the coaches to the female taekwondo athletes in the sports environment increased the trait and state sport confidence of the female athletes, it did not change the level of the trait and state sport confidence of male athletes.